Volumetric analysis of hippocampus and amygdala in animal model of PTSD - Ivanisevic, Milica; Knezevic, Milica; Kojovic, Natalija; Starcevic, Ana (Medicinski podmladak, 2022)
Introduction: Posttraumatic stress disorder represents a mental disorder that occurs after life threatening situations. Animal models in psychiatry studies represent a base from which results and conclusions can be translated to human population. Amygdala and hippocampus are important neuroanatomical substrates possibly relevant to PTSD pathogenesis. Aim: The aim of study was to investigate volumetric changes that occur in these neuroanatomical substrates related to PTSD animal model.Materials and methods: Experiment was conducted on adult male Wistar rats. They were two groups, experimental and control. Experimental paradigm lasted for 31 days during which animals were exposed to acute and chronic stress. Acute stress was performed on the first day and ten days later. It was conducted by exposing rats to cat odor during immobilization in plastic tubes. In between, animals were exposed to chronic social stress by pair rotations. After second acute stress exposure, experimental group was divided in two subgroups from which one received dexamethasone dose. After the experiment ended, animals were sacrificed and the brain was extracted. Following the freezing process, brain tissue samples were cut and prepared for microscopy using Nissl staining. This was followed by volumetric analysis of hippocampus and amygdala. Measurements were performed bilaterally using Image Tool 3.0 Software.Results: Results showed volumetric changes in these structures. Hippocampus had smaller volume in the experimental subgroup without dexamethasone (X=0.6144) compared to the control group (X=0.9688). Amygdala as well had smaller volumes in same subgroup compared to the control (X=10.0156 compared to X=11.5041). Conclusion: Our study provided results in agreement with several previous studies on rodents and contributes to the assumption that hippocampus and amygdala have significance in PTSD etiology. We find contribution to animal models important while PTSD. Further goal is to expand our study which will help us to better understand the disorder itself. Keywords: amygdala, animal model, hippocampus, volumetric analysis, posttraumatic stress disorder
Keywords: amygdala; animal model; hippocampus; volumetric analysis; posttraumatic stress disorder